Innovative education management: an empirical study - Mateu, Guillermo (2021)
This paper analyzes the impact of innovative education tools—in this case, based on experimental methodology—on the acquisition of theoretical knowledge among management students. The study incorporates a clear split-sample design using two equivalent, randomly created groups. One group participates in a classroom experiment designed to illustrate the concept of the Phillips Curve, while the other participated in a traditional non-experimental lesson. The experiment is implemented under a strict protocol, while results’ evaluation is based on the comparison of post-experiment academic performance, which guarantees full anonymity and privacy of decisions. This design analyzes the impact of the classroom experiment between the two groups. Students who participated in the Phillips Curve experiment demonstrated superior academic performance, thus confirming that innovative management tools are conducive to superior academic performance. Educators should consider this type of pedagogical tool as an integral part of their teaching method. The clear design and robust findings of this article confirm the role of innovative management education on academic performance.